Computer Modeling of Burning Ceramic Stone Charge Taking into Account Natural Air Convection Inside of Charge - A. N. Chichko; A. S. Borozdine; S. G. Likhouzov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
A three-dimensional mathematical model for numerical modeling of burning process intended for a brick charge. The model presupposes natural air convection inside of the charge for tunnel ovens. Computer modeling of burning process for a charge fragment by specified temperature curve has been carried out. Calculations of temperature field taking place in the area of charge fragment are presented in the paper.